2002
DOI: 10.1681/asn.v132536
|View full text |Cite
|
Sign up to set email alerts
|

Open Randomized Trial Comparing Early Withdrawal of either Cyclosporine or Mycophenolate Mofetil in Stable Renal Transplant Recipients Initially Treated with a Triple Drug Regimen

Abstract: ABSTRACT. Cyclosporine (CsA) is the current primary immunosuppressant for the prevention of renal allograft rejection. Its chronic use is associated with various adverse effects like hypertension, hyperlipidemia, and nephrotoxicity, which in turn may contribute to chronic allograft nephropathy and cardiovascular mortality. This study compares a CsA-free maintenance regimen of mycophenolate mofetil (MMF) and corticosteroids with CsA and corticosteroids after early conversion from triple drug therapy. Eighty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…They also found more biopsy-proven chronic rejection in the CsA withdrawal arm by 2 years post-transplant. Schnuelle et al randomized 84 patients to either CsA or MMF withdrawal after 3 months (6). Those who underwent CsA withdrawal remained on 2 g/d MMF as prednisolone was temporarily increased to 25 mg/d and slowly tapered thereafter.…”
Section: Early Trials On Cni Withdrawal Without Mpa Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found more biopsy-proven chronic rejection in the CsA withdrawal arm by 2 years post-transplant. Schnuelle et al randomized 84 patients to either CsA or MMF withdrawal after 3 months (6). Those who underwent CsA withdrawal remained on 2 g/d MMF as prednisolone was temporarily increased to 25 mg/d and slowly tapered thereafter.…”
Section: Early Trials On Cni Withdrawal Without Mpa Monitoringmentioning
confidence: 99%
“…Despite the disappointing results of these first studies in terms of the rejection risk, they showed that patients in whom CsA withdrawal was successful had better renal function, blood pressure, and lipid profile than those remaining on CsA (5)(6)(7)9,10). This encouraged researchers not to abandon the goal of CNI withdrawal, but to better identify predictors of AR and to find a way to optimize the maintenance dose of MMF and steroids.…”
Section: Early Trials On Cni Withdrawal Without Mpa Monitoringmentioning
confidence: 99%